SPE Asia Pacific Oil &Amp; Gas Conference and Exhibition 2006
DOI: 10.2118/100989-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Neural Network Approach to Reservoir Permeability Estimation from Well Logs

Abstract: Reservoir permeability is one of the most important properties of oil and gas fields for reservoir characterization. In un-cored intervals or wells, reservoir description and evaluation methods using well log data represent a significant technical as well as economic advantage because well logs can provide a continuous record over the entire well where coring is impossible. Permeability determination from well logs in heterogeneous formation has a difficult and complex problem to solve by conventional statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This formation is one of important hydrocarbon reservoirs in Zagros Basin. Sarvak Formation is placed on Kazhdomi Formation conformably; whereas, the upper boundary of it with Ilam Formation is erosional unconformable [12]. This formation is made of limestone and has a major porosity with fracture type [13].…”
Section: Geology Of Studied Oil Formationmentioning
confidence: 99%
“…This formation is one of important hydrocarbon reservoirs in Zagros Basin. Sarvak Formation is placed on Kazhdomi Formation conformably; whereas, the upper boundary of it with Ilam Formation is erosional unconformable [12]. This formation is made of limestone and has a major porosity with fracture type [13].…”
Section: Geology Of Studied Oil Formationmentioning
confidence: 99%
“…Lim and Kim (2004) demonstrated that fuzzy logic and ANN can be utilized as a powerful tool to determine reservoir properties from well logs. Lim et al (2006) also introduced a hybrid method combining PNN (polynomial network) and GA (genetic algorithm) as a new neural network approach. Kumar (2012) used well logs and seismic data as the input parameters for ANN, and highlighted the efficiency of ANN in obtaining nonlinear systems and models for reservoir characterization problems.…”
Section: Introductionmentioning
confidence: 99%